HISTORY OF FEMINIST PERSPECTIVE AND FEMALE PARTICIPATION IN WORK FORCE IN INDIA - Dr. Shumayela Hasan (International Engineering Journal For Research & Development, 2021)
Feminism has been much talked about in the modern era, especially due to the increased awareness and education that led to the realisation of women's rights and justice. Women are no longer ready to submit themselves to harassment and demand relationships on equitable principles. UN has played an important role by organising 4 world conferences on women in 1975,1980, 1985,and 1995 Various critical areas were recognised and strategies were formulated to fight against violence, poverty and empowering the women to take their decisions and promote their health. For this purpose the Commission on the Status of Women has been instrumental in portraying the reality of women’s lives and working toward gender equality .UN has also included gender equality in its 17 Sustainable development goals ,ensuring legal and legislative changes for women’s rights. Every year Many theories and views have been presented till date on what is feminism and gender equality since the times immemorial. The perspectives of different thinkers and writers have gone to make a huge impact on how we think about feminism in today’s modern perspective, thus acting as a blueprint in our minds of how feminism was shaped over time. This paper is a compilation of the literature review on how feminism evolved over time and in what shape does it exist in the society today